PRAKTIK MANAJEMEN OPERASIONAL DI PERUSAHAAN MANUFAKTUR ELEKTRONIK ZUANBAO - Fendy Cuandra; Angelina; Caroline Marninda; Lian Andrianus; Septriana; Titan Martinus (JURNAL KREASI RAKYAT, 2023)
This research was conducted to determine the implementation of operational management aspects in the Zuanbao manufacturing company. The research was conducted by utilizing qualitative methods in the form of literature studies and interviews with informants where the informant was the production head of connector products at the Zuanbao manufacturing company. Of the 10 aspects of operational management which include supply chain management, quality, and process strategy, Zuanbao as a manufacturing company that can be categorized as a large company has management and processes that apply to the company so that operational activities take place efficiently and effectively according to company expectations.